Navigating HIV prevention policy and Islam in Malaysia: contention, compatibility or reconciliation? Findings from in-depth interviews among key stakeholders - Barmania, Sima (BMC Public Health, 2016)
BACKGROUND: Malaysia is a multicultural society, predominantly composed of a Muslim majority population, where Islam is influential. Malaysia has a concentrated HIV epidemic amongst high risk groups, such as, Intravenous Drug Users (IVDU), sex workers, transgender women and Men who have sex with Men (MSM). The objective of this study is to understand how Islam shapes HIV prevention strategies in Malaysia by interviewing the three key stakeholder groups identified as being influential, namely the Ministry of Health, Religious leaders and People living with HIV. METHODS: Thirty-Five in depth semi structured interviews were undertaken with religious leaders, Ministry of Health and People living with HIV in the last half of 2013 using purposive sampling. Interviews adhered to a topic guide, were audiotaped, and transcribed verbatim and analyzed using a framework analysis. RESULTS: Themes including the importance of Islam to health, stakeholder relationships and opinions on HIV prevention emerged. Islam was seen to play a pivotal role in shaping strategies relating to HIV prevention in Malaysia both directly and indirectly. Stakeholders often held different approaches to HIV prevention, which had to be sensitively considered, with some favouring promotion of Islamic principles, whilst others steering towards a more public health centred approach. CONCLUSIONS: The study suggests that Islam indeed plays an important role in shaping health policies and strategies related to HIV prevention in Malaysia. Certainly, stakeholders do hold differing viewpoints, such as stances of what constitutes the right approach to HIV prevention. However there are also areas of broad consensus, such as the importance in Islamic tradition to prevent harm and disease, which can be crafted into existing and future HIV prevention strategies in Malaysia, as well as the wider Muslim world.